Mitochondria and Brain Disorders - Baloyannis, Stavros (IntechOpen, 2020)
The mitochondrion is a unique and ubiquitous organelle that contains its own genome, encoding essential proteins that are major components of the respiratory chain and energy production system. Mitochondria play a dominant role in the life and function of eukaryotic cells including neurons and glia, as their survival and activity depend upon mitochondrial energy production and supply. Besides energy production, mitochondria also play a vital role in calcium homeostasis and may induce apoptosis by excitotoxicity. Mitochondrial dysfunction is related to common neurological diseases, such as Parkinson's disease, Alzheimer's disease, Friedreich's ataxia, Huntington's disease, and Multiple Sclerosis. An efficient treatment of mitochondrial dysfunction would open new horizons in the therapeutic perspectives of a substantial number of inflammatory and degenerative neurological disorders.